Strategy Safari / A Guided Tour Through the Wilds of Strategic Management - Ahlstrand Bruce; Lampel Joseph; Mintzberg Henry (Prentice Hall, 1998)
A thoughtful and readable field guide to the wilds of strategic management. Embarkation, And Over Here Ladies and Gentlemen: The Strategic Management Beast, The Design School, The Planning School, The Positioning School, The Entrepreneurial School, The Cognitive School, The Learning School, The Power School, The Cultural School, The Environmental School, The Configuration School, ''Hang On Ladies and Gentlemen: You Have Yet to Meet the Whole Beast'', References, Index.